The promise of solar power - Stonebarger, Bill; Zeibel, Ken; Hawkhill Associates Inc. (Wisconsin : Hawkhill Associates Inc., 2005)
Features an interview with Ken Zweibel, solar volataic engineer at the National Renewable Energy Laboratory in Golden, Colorado. The video explores the potential uses of solar power technologies in the 21st century
Title from title screen
Videography, Jane Denny, Michael Stonebarger, Bill Stonebarger ; editors, Bill Stonebarger, Michael Stonebarger ; music, Michael Stonebarger
Keywords: Solar energy; Renewable energy sources